Treatment profiles in the public dental service of Northern Norway - Karlsen, Guro (Universitetet i Tromsø, 2012)
Introduction: The Public Dental Service in Norway has changed during the last decades. Dental hygienists have increased in numbers, but how this has influenced the organization of the patient treatment at the clinics is not well known. Aim: The aim of this study was to investigate the organization of the work-day in the Public Dental Service in Northern Norway in terms of who is being treated and what treatment is being performed. The aim was also to explore how the patients are distributed between dentists and dental hygienists. Method: A self-report questionnaire was sent to dentists and dental hygienists at three different clinics in each of the three northern counties of Norway. Interviews with some of the clinic managers of the participating clinics were also performed. Results: Time spent on each patient was relatively high. Dentists provided mostly reparative treatments on adult population, but with some variation in treatment provided in different counties. Dental hygienists did more preventive treatments on children (aged 0-18). Conclusions: Treatments performed across the three counties were relatively similar. Dentists mainly provide restorative treatments, dominated by dental fillings. Dental hygienists mainly provided examinations and preventive treatments, with the majority of patients being children. Through the study, it clearly appears that patients of age 18 or below dominate the Public Dental Service. This study shows a need for further studies to reveal what future challenges the Public Dental Service is facing in terms of models of organization and delegation of treatments.